2007
DOI: 10.1016/j.foreco.2007.06.035
|View full text |Cite
|
Sign up to set email alerts
|

The effects of afforestation and cultivation on water yield in the Andean páramo

Abstract: Over the last decades, the Andean highlands of Ecuador have been characterised by intense afforestation efforts, in order to increase the economic return of less viable agricultural areas, reduce erosion and, more recently, to sequestrate atmospheric carbon. Afforestation with Pinus species is widespread in the high altitudinal grasslands known as páramos. The impact of Pinus patula afforestation on the water yield is studied and compared to the more common practice of intensive grazing and potato cultivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
166
3
23

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(202 citation statements)
references
References 32 publications
10
166
3
23
Order By: Relevance
“…In addition to the relatively sparse canopy of mature P. patula trees, the relatively low ET in the mature P. patula stand was in part attributable to previous selective logging activities that had reduced stand basal area. Thus, from a purely hydrologic services standpoint, planting of native pine trees on degraded pasture areas at this site did not produce a dramatic increase in ET or reductions in water yield, in contrast to findings reported elsewhere (Farley et al 2005, Buytaert et al 2007, Huber et al 2008, Wang et al 2008, Little et al 2009). Notwithstanding, the higher infiltration rates recorded for pine stands versus grazed pasture suggests a positive impact of pine reforestation on soil hydraulic properties, which should enhance subsurface recharge and therefore baseflow as long as ET losses remain comparable (Muñoz-Villers et al 2015).…”
Section: Introductioncontrasting
confidence: 87%
“…In addition to the relatively sparse canopy of mature P. patula trees, the relatively low ET in the mature P. patula stand was in part attributable to previous selective logging activities that had reduced stand basal area. Thus, from a purely hydrologic services standpoint, planting of native pine trees on degraded pasture areas at this site did not produce a dramatic increase in ET or reductions in water yield, in contrast to findings reported elsewhere (Farley et al 2005, Buytaert et al 2007, Huber et al 2008, Wang et al 2008, Little et al 2009). Notwithstanding, the higher infiltration rates recorded for pine stands versus grazed pasture suggests a positive impact of pine reforestation on soil hydraulic properties, which should enhance subsurface recharge and therefore baseflow as long as ET losses remain comparable (Muñoz-Villers et al 2015).…”
Section: Introductioncontrasting
confidence: 87%
“…The wetlands, which mainly comprise small lakes or seasonally and permanently saturated terrain, vary considerably in area (Table 2). Although they are important in generating runoff [60], the wetlands were not mapped as their area is relatively small compared to páramo and native forest, and the climatological and hydrological data required to explain their fluctuations were not available to the researchers at the time the research was carried out. Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Wagnon et al (1999) Characterizing evapotranspiration from non-glacierized surfaces has equally been a challenge and studies are limited due to lack of meteorological data. Buytaert et al (2007) and Córdova et al (2015), suggested values between 1.8 and 2.0 mm d A reduction of glacier cover will therefore reduce streamflow, because of increased evapotranspiration from newly ice-free areas (Frans et al, 2015). However, this effect tends to reduce quickly with catchment size and distance from the glacier terminus.…”
Section: Hydrologic (Water Supply-side) Projectionsmentioning
confidence: 99%